Brief ELT in Digital Classroom for Lazy Creative Lecturers (Option After Post Pandemic Recovery): Lecturers’ Perspectives - Triana, Yunika; Nugroho, Arif (Indonesian Journal of EFL and Linguistics, 2021)
This paper provides essential information for lecturers and educational institutions to think creatively in teaching English via online. The rapid development of Information and Communication Technology (ICT) and the Covid-19 emergency made lecturers and educational institutions think harder than usual. Higher education has used a powerful learning pattern and strategic policy to overcome the problem namely structure and unstructured online learning platform. The research aimed to find what platform is suitable in higher education and how lecturers create particular activity using HOTs to make students to think creatively. It also underlined that this new platform provides useful options that not only offers material delivery features but also an interactive communication feature. There were selected 10 lecturers of ELT in higher education level being interviewed and separated into two group users of structured and unstructured digital learning models. The distribution was based on their experience on teaching English using both models. This study analyzed interviews with lecturers who are experienced in usage of structured and unstructured online Learning platform. The findings were discussed by resuming and then drawing the conclusion through interpreting the findings. The findings from these data illustrated that these new learning patterns had a significant impact on students' cognitive and psychomotor abilities. Moreover, this model also significantly affected institution quality control.